(untitled) (American Journal of Islam and Society, 2022)
New Muslim movements in South India, such as the Solidarity Youth movement, re-formulated Muslim priorities towards human rights, democracy, development, environmental activism, and minorities. I read Solidarity Youth Movement as proposing an ethic of Islam’s conception of justice, while also drawing inspiration from the influential Islamist Abul A’la Maududi. Focusing on jurisprudential debates, I look at the ways in which Maududi’s intervention informs the praxis of Solidarity Youth Movement. This paper seeks the possibility of examining their activism as an instance of juristic deliberation, linked to the revival of maqāṣid al-sharī’ah in the latter part of the twentieth century. I suggest a reading of their maqāṣid approach, born out of praxis in a Muslim minority context, as potentially informing the development of fiqh al-aqalliyah.